Consumption of Bottled Water at the Bottom of the Pyramid: Who Purchases First?. (March 2020) - Howell, Rachel; Sinha, Kinsuk Mani; Wagner, Natascha; Doorn, Neelke; van Beers, Cees
While consumer and marketing research in developed markets is an established field, research on consumers in an Bottom of the Pyramid (BoP) setting is less established and mostly conceptual or qualitative. This paper examines the individual heterogeneity and the local context of BoP consumers with an empirical study on consumption of low cost bottled water on the Kenyan coast and the capitals of Uganda and Rwanda. The empirical analysis builds on existing research exploring consumer behavior, and it studies a database of 713 bottled water consumers in Kenya, Uganda and Rwanda. Consumers with a higher level of education were less likely to be late consumers. Additionally, early consumers were more likely to purchase due to a purposeful search for a bottled drinking water solution. Since we control for location specific effects we highlight the importance of supply driven consumption in the BoP market. Furthermore, the results suggest that the two water companies may not be reaching their targeted low-income consumers but rather middle class consumers. The research contributes to the larger BoP debate by presenting evidence that consumers in a BoP setting may purchase more on the basis of supply of a product rather than other socio-demographic factors such as income.